New insights in the relative radiobiological effectiveness of proton irradiation - Ilicic, K.; Combs, S. E.; Schmid, T. E. (Radiation Oncology, 2018)
Background: Proton radiotherapy is a form of charged particle therapy that is preferentially applied for the treatment of tumors positioned near to critical structures due to their physical characteristics, showing an inverted depth-dose profile. The sparing of normal tissue has additional advantages in the treatment of pediatric patients, in whom the risk of secondary cancers and late morbidity is significantly higher. Up to date, a fixed relative biological effectiveness (RBE) of 1.1 is commonly implemented in treatment planning systems with protons in order to correct the physical dose. This value of 1.1 comes from averaging the results of numerous in vitro experiments, mostly conducted in the middle of the spread-out Bragg peak, where RBE is relatively constant. However, the use of a constant RBE value disregards the experimental evidence which clearly demonstrates complex RBE dependency on dose, cell- or tissue type, linear energy transfer and biological endpoints. In recent years, several in vitro studies indicate variations in RBE of protons which translate to an uncertainty in the biological effective dose delivery to the patient. Particularly for regions surrounding the Bragg peak, the more localized pattern of energy deposition leads to more complex DNA lesions. These RBE variations of protons bring the validity of using a constant RBE into question. Main body: This review analyzes how RBE depends on the dose, different biological endpoints and physical properties. Further, this review gives an overview of the new insights based on findings made during the last years investigating the variation of RBE with depth in the spread out Bragg peak and the underlying differences in radiation response on the molecular and cellular levels between proton and photon irradiation. Research groups such as the Klinische Forschergruppe Schwerionentherapie funded by the German Research Foundation (DFG, KFO 214) have included work on this topic and the present manuscript highlights parts of the preclinical work and summarizes the research activities in this context. Short conclusion: In summary, there is an urgent need for more coordinated in vitro and in vivo experiments that concentrate on a realistic dose range of in clinically relevant tissues like lung or spinal cord.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Bragg peak; Proton; Radiotherapy; RBE